Analysis of Language Functions in Interpersonal Communication in the English Visual Novel Game Phoenix Wright: Ace Attorney - Pipit, Mayang; Yudhistira, Mahesa (STKIP PGRI Tulungagung, 2025)
The purpose of this study is to analyze the language functions in the visual novel Phoenix Wright: Ace Attorney by Shu Takumi using Jakobson's (1960) theory of language functions. This research employs a qualitative descriptive method to examine the data. Based on the analysis, the researchers identified four of the six language functions proposed by Jakobson within the visual novel. The most dominant language function found is the conative function, with the highest percentage of 24 instances (36.4%). The second most frequent is the referential function, which appears in 19 instances (28.8%). The emotive function ranks third, with 14 instances (21.2%). Lastly, the phatic function appears the least, with 9 instances (13.6%). These findings indicate that the conative function plays a central role in the visual novel, highlighting its focus on influencing the listener's actions or responses. The presence of other functions, such as referential, emotive, and phatic, also reflects the dynamic and interactive nature of the dialogue in Phoenix Wright: Ace Attorney.